2021
DOI: 10.1177/1535370221996655
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma application enhances the recovery of transected sciatic nerves in rats

Abstract: This experimental research aimed to investigate the effects of non-thermal plasma on nerve regeneration after transected nerve damage using the sciatic nerve in Wistar albino (A) rats. The experiments were performed on 27 Wistar A rats. The rats underwent surgery for right sciatic nerve exposure and were divided into three groups (each group, n = 9) according to sciatic nerve transected injury (SNTI) and non-thermal plasma application: a non-nerve damage (non-ND) group, a only nerve damage without non-thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Previously, a technique called nozone (no-ozone) cold plasma (NCP) was developed in which argon gas is used to minimize the generation of ozone and NO compounds. Recently, an NCP device that allows for non-thermal plasma to be used in even more applications has been developed by Feagle Co., Ltd. (Yangsan, Korea); this device is unique, in that it only produces a very small amount of ozone, and it can maintain a temperature of 35 °C or lower [ 25 ]. This capability is important for studying the effects of NCP because using this technology in the oral cavity requires the plasma to be created with minimal generation of ozone and NO compounds that may harm the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a technique called nozone (no-ozone) cold plasma (NCP) was developed in which argon gas is used to minimize the generation of ozone and NO compounds. Recently, an NCP device that allows for non-thermal plasma to be used in even more applications has been developed by Feagle Co., Ltd. (Yangsan, Korea); this device is unique, in that it only produces a very small amount of ozone, and it can maintain a temperature of 35 °C or lower [ 25 ]. This capability is important for studying the effects of NCP because using this technology in the oral cavity requires the plasma to be created with minimal generation of ozone and NO compounds that may harm the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results are similar to those of previous studies that inflicted crushing and cut injury on the sciatic nerve. In the NCP-treated group, MBP, NF-200, GAP-43, S100B, and tau, which are involved in axonal regeneration, were increased, and CD68 and MAP2, which have negative effects on regeneration, were decreased [33].…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, after inflicting crush or cut injury to the sciatic nerve of rats, NCP was applied to investigate the therapeutic effect [33]. These studies revealed that the function recovery and neuronal regeneration greatly improved after plasma application.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). In all experiments, treatment with NTP was applied at 2.0 slm for 5 min 14 16 .
Figure 1 The NTP-generating device.
…”
Section: Methodsmentioning
confidence: 99%